Nutritional profiling of stingless bee bread (Meliponini) across species and sites in Riau, Indonesia - ENI SUHESTI; YELMIZA YELMIZA; DITA FITRIANI; HADINOTO HADINOTO (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Suhesti E, Yelmiza, Fitriani D, Hadinoto. 2025. Nutritional profiling of stingless bee bread (Meliponini) across species and sites in Riau, Indonesia. Biodiversitas 26: 6151-6161. Stingless bee bread is a nutrient-dense fermented pollen increasingly promoted as a functional food, yet Indonesian nutritional datasets remain scarce. This study characterizes proximate composition and vitamins A, B2, and E in bee bread from three stingless bee species (Geniotrigona thoracica, Heterotrigona itama, and Trigona apicalis) managed by smallholders at multiple sites in Riau, Indonesia. For each species × site combination, bee-bread pots were pooled to obtain a homogenized composite, which was summarized on a unified fresh-mass basis. Group differences among species and sites were evaluated using non-parametric tests. At a co-occurring site, G. thoracica consistently exhibited the highest levels of vitamins A, B₂, and E; T. apicalis showed the highest total fat and fat-derived energy; and H. itama combined relatively high total energy with elevated protein. Within H. itama, site effects were evident, with vitamins A and E peaking at specific locations and vitamin B₂ at another. These patterns resolve into three practical nutritional signatures, vitamin-oriented in G. thoracica, lipid-oriented in T. apicalis, and relatively stable energy or protein in H. itama. While the pooled composite design constrains colony-level inference, the species- and site-resolved ranges reported here provide preliminary nutritional baselines that can inform future work on quality control and biodiversity-aligned meliponiculture.